2014
DOI: 10.1007/s12013-014-0271-3
|View full text |Cite
|
Sign up to set email alerts
|

Tegillarca granosa Extract Haishengsu Induces Apoptosis in Human Hepatocellular Carcinoma Cell Line BEL-7402 Via Fas-Signaling Pathways

Abstract: This study was designed to investigate the apoptosis-inducing properties of Tegillarca granosa extract Haishengsu (HSS) in human hepatocellular carcinoma cell line BEL-7402. Proliferation inhibition of the human hepatocellular carcinoma BEL-7402 cells was determined by the MTT assay, and the cell viability was determined by trypan blue dye exclusion assay. Apoptosis of BEL-7402 cells was demonstrated by fluorescence microscope with flow cytometry with Annexin V-FITC/PI double staining and Hoechst 33258 stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(41 reference statements)
1
7
0
Order By: Relevance
“…Our previous research demonstrated that HSS induces apoptosis of BEL-7402 cells, as determined by flow cytometric analysis and Hoechst 33258 nuclear staining (15). To further confirm these results, a DNA fragmentation assay was conducted, since DNA fragmentation is a classical hallmark of apoptosis.…”
Section: Hss Induces Apoptosis Of Bel-7402 Cellsmentioning
confidence: 71%
See 3 more Smart Citations
“…Our previous research demonstrated that HSS induces apoptosis of BEL-7402 cells, as determined by flow cytometric analysis and Hoechst 33258 nuclear staining (15). To further confirm these results, a DNA fragmentation assay was conducted, since DNA fragmentation is a classical hallmark of apoptosis.…”
Section: Hss Induces Apoptosis Of Bel-7402 Cellsmentioning
confidence: 71%
“…Tegillarca granosa as described previously (15), and dissolved in phosphate-buffered saline (PBS) prior to use.…”
Section: Hss Preparation Hss Was Extracted From the Shellfishmentioning
confidence: 99%
See 2 more Smart Citations
“…The natural products may have an adjuvant effect when added to conventional chemotherapy in patients with cancers [1,2]. Haishengsu (HSS) is a purified protein from Tegillarca granosa L. (Order Arcoida) which is a sea creature that contains a high concentration of proteins and vitamin B 12 [3][4][5][6][7][8][9][10][11]. When used as an adjuvant therapy, HSS was reported to improve clinical outcomes of patients undergoing conventional chemotherapy for lung or renal cancer [2,8].…”
Section: Introductionmentioning
confidence: 99%